Successful restart of chemotherapy in a patient with primary mediastinal nonseminomatous germ cell tumor after COVID‐19 infection. Issue 18 (28th July 2022) - Tanabe, Yuki; Shukuya, Takehito; Nagata, Yuichi; Watanabe, Takayasu; Seto, Koichi; Takahashi, Rina; Masuda, Koichi; Miura, Keita; Tajima, Ken; Hiki, Makoto; Hayashi, Takuo; Suzuki, Kenji; et al.
Abstract: Cancer patients are considered highly susceptible to severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection. However, it is not well known when chemotherapy can be safely restarted in cancer patients after coronavirus disease 2019 (COVID‐19). Here, we describe the case of an 18‐year‐old man diagnosed with primary mediastinal nonseminomatous germ cell tumor (PMNSGCT) in which chemotherapy could be safely restarted after COVID‐19. On day 11 of the third cycle of bleomycin, etoposide, plus cisplatin (BEP), he was diagnosed with mild COVID‐19. On day 16 after the onset of COVID‐19 (day 26 of third cycle of BEP), chemotherapy for his PMNSGCT was restarted. He received surgery after the fourth cycle of BEP without recurrence of COVID‐19. Chemotherapy could be restarted and followed by surgery in this post‐COVID‐19 patient who had experienced mild illness after the discharge criteria were met and all symptoms had disappeared. We report this case with a review of the literature on restarting chemotherapy after SARS‐CoV2 infection. Abstract : It is not well known when chemotherapy can be safely restarted in cancer patients after coronavirus disease 2019 (COVID‐19). Here, we present the case of an 18‐year‐old man who was diagnosed with a primary mediastinal nonseminomatous germ cell tumor (PMNSGCT) and BEP (bleomycin, etoposide, plus cisplatin chemotherapy) for the tumor could be safely restarted after COVID‐19. On day 11 of the third cycle of BEP, he was diagnosed with mild COVID‐19. On day 16 after the onset of COVID‐19 (day 26 of third cycle of BEP), chemotherapy for his PMNSGCT was restarted. Four cycles of BEP were completed without recurrence of COVID‐19. Chemotherapy was restarted in this post‐COVID‐19 patient who had experienced mild illness after the discharge criteria were met and all symptoms had disappeared. We report this case with a review of the literature on restarting chemotherapy after SARS‐CoV2 infection.